Resurrecting immortal‐time bias in the study of readmissions. (26th December 2019) - Hugar, Lee A.; Borza, Tudor; Oerline, Mary K.; Hollenbeck, Brent K.; Skolarus, Ted A.; Jacobs, Bruce L.
Abstract: Objective: To compare readmission rates as measured by the Centers for Medicare and Medicaid Services and the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) methods. Data Sources: 20 percent sample of national Medicare data for patients undergoing cystectomy, colectomy, abdominal aortic aneurysm (AAA) repair, and total knee arthroplasty (TKA) between 2010 and 2014. Study Design: Retrospective cohort study comparing 30‐day readmission rates. Data Collection/Extraction Methods: Patients undergoing cystectomy, colectomy, abdominal aortic aneurysm repair, and total knee arthroplasty between 2010 and 2014 were identified. Principal Findings: Cystectomy had the highest and total knee arthroplasty had the lowest readmission rate. The NSQIP measure reported significantly lower rates for all procedures compared to the CMS measure, which reflects an immortal‐time bias. Conclusions: We found significantly different readmission rates across all surgical procedures when comparing CMS and NSQIP measures. Longer length of stay exacerbated these differences. Uniform outcome measures are needed to eliminate ambiguity and synergize research and policy efforts.